EFEKTIVITAS KELAS IBU HAMIL TERHADAP PENGETAHUAN DETEKSI DINI TANDA BAHAYA KEHAMILAN - Elmeida, Ika Fitria; Nurlaila, Nurlaila; Nurchairina, Nurchairina; Dwi Sri Isnawati, (Journal of Innovation Research and Knowledge, 2023)
The purpose of the pregnant women class' is to increase the knowledge and skills of pregnant women which is carried out four times. Lack of knowledge about the danger signs of pregnancy will have an impact on complications for the mother which will result in late referrals. In PMB Dwi Sri Isnawati in the last two years, there were 7 cases of hypertension, 6 cases of premature rupture of membranes (PROM), 10 cases of hyperemesis gravidarum, and 6 cases of anemia. Based on a preliminary study of 10 pregnant women, 4 people know the danger signs of pregnancy and 6 people do not know the specifics. This research objective was to determine the effectiveness of pregnant women's classes on knowledge of early detection of pregnancy danger signs at PMB Dwi Sri Isnawati in Mojopahit Village of Punggur Sub-District Central Lampung Regency in 2021. The design used in this research was pre-experimental by using the one-group pretest-posttest design approach. The population in this study was 20 pregnant women in the first trimester, with a total population sample technique. Bivariate analysis in this study used the Wilcoxon test. The results of the Wilcoxon Signed Rank Test show the Asym value. sig.2-tailed of 0.001 < (α = 0.05) which means that there is an effect of pregnant women's class on the knowledge of early detection of danger signs of pregnancy at PMB Dwi Sri Isnawati in Mojopahit Village of Punggur Sub-District Central Lampung Regency in 2021. It is recommended to provide support so that pregnant women and their families attend classes for pregnant women on a regular basis